Teachers’ Academic Behaviors on Students’ Academic Achievement - Subedi, Kusum Raj; Shrestha, Sita Kumari; Subedi, Suprabha (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2024)
Teacher's behavior plays a vital role in academic achievement. A teacher's behavior can affect student's capacity to learn as well as others students' learning environment. Teachers are the role models for their students and their behavior meaningfully influence students’ personal and academic life. Keeping in view the significant influence of teachers on the students’ academic achievement, the study aimed to investigate the influence of teachers’ behavior on students’ academic achievement at affiliated campuses. This article explores the correlation between teachers' actions, methods, attitudes, and behaviors in the academic setting and how they impact students' academic performance and achievement. It delves into the importance of teacher-student interactions, instructional strategies, feedback mechanisms, and classroom management techniques in shaping students' learning outcomes. This research article discusses the Influence of Teachers’ Behavior on Students Academic Achievement of Higher Level. The respondents were the teachers and students were associated to the campuses affiliated to Tribhuvan University. From the 15 public colleges, 60 teachers and 600 students from five departments were selected as a sample. Two questionnaires were developed and validated through pilot testing and administered to the sample for the collection of data. The researcher personally visited the respondents, thus 100% data were collected. The collected data were tabulated and analyzed by using chi-square and Pearson's product moment coefficient of correlation (r). The major conclusions of the study were that teachers felt proud to be teachers; they adjusted themselves with the prevailing situation and circumstances, and they used different motivational techniques for teaching. Students were found to be satisfied with the positive behavior of their teachers. The relationship between the teachers' behavior and corresponding academic achievement (marks) revealed a highly positive significant correlation.